Impact of tillage systems on maize emergence - Sojnóczki, István; Nagy, János; Kecskés, István (Acta Agraria Debreceniensis, 2023)
In Europe, there has been a significant change in the way tillage is approached in recent years. This change is due to a growing awareness among farmers, politicians and society as a whole that soil is not a renewable resource in itself. From an agricultural point of view, the greatest impact on soil condition can be achieved through the use of the applied tillage systems.  My research takes this approach as a basis when examining the different tillage systems and their impact on the environment. In this context, conventional and a variety of no-tillage systems are examined in this paper. As a next step, it is examined how the environmental conditions created by the different tillage systems influence the emergence of maize hybrids. The analyses are carried out in a multi-factorial, long-term tillage field experiment. The same batch of the same hybrid seed was sown in several crop years, and the effects of environmental conditions on the emergence process were examined. Environmental effects and emergence-related uptake were measured in the examined plots. Measurements of environmental effects included air temperature, precipitation, soil temperature measured at seeding depth, as well as % cover of stem residue on the surface in the treated plots. The first emergence time measurements of the sown crop in the plots of each treatment were compared and relationships between these factors were investigated.